An Investigation of Antibiotic Resistance of Aggregatibacter Actinomycetemcomitans and Porphyromonas Gingivalis in Peri-implantitis Lesions - Zeinab Kadkhoda; Sepehr Torabi; Amir Aliramezani (Islamic Dental Association of Iran, 2017)
Background and Aim: It has been shown that anaerobic and capnophilic bacteria play an important role in implant failure and loss. The present study is an in vitro research aimed to investigate the antibiotic resistance of Aggregatibacter actinomycetemcomi-tans (Aa) and Porphyromonas gingivalis (Pg) in peri-implantitis lesions of Iranian pa-tients and to find laboratory efficiency of some antibiotic on these two bacteria. Materials and Methods: In this antibiogram study, the plaque samples were obtained from peri-implantitis lesions from patients who referred to implant center of Faculty of Dentistry of Tehran University of Medical Sciences. Nine samples incubated in Aa-specific culture media and 9 samples incubated in Pg-specific culture media under anaerobic and capnophilic conditions. After 48 hours, colonies were verified by microscopic and biomedical examination, and a colony-counting device. Then the specimens were cultured in the specific culture media for antibiogram evaluations by measuring the diameter of growth inhibition zone of antibiotic standard disks of amoxicillin, co-amoxiclav, metronidazole, tetracycline, clindamycin, and ciprofloxacin. Results: There was no statistically significant difference (P=0.74) between the colony count of Aa (84.56±16.65) and Pg (87.67± 21.49). Most of growth inhibition zone ranged between 10 and 35 mm. The Pg specimens were significantly more resistant to studied antibiotics (P0.05) compared to Aa. However, both groups had similar resistance to amoxicillin and tetracycline, P-values were 0.22 and 0.13 respectively. Conclusion: A large number of peri-implantitis lesions contain Aa and Pg bacteria. Moreover, the majority of Aa samples were sensitive to the applied antibiotics, while almost all Pg specimens were resistant to them.